1998
DOI: 10.1002/1529-0131(199807)41:7<1275::aid-art19>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Reduced progression of experimental osteoarthritis in vivo by selective inhibition of inducible nitric oxide synthase

Abstract: Objective. To evaluate the in vivo therapeutic efficacy of N-iminoethyl-L-lysine (L-NIL), a selective inhibitor of inducible nitric oxide synthase (iNOS), on the progression of lesions in an experimental osteoar-thritis (OA) dog model. The effect of L-NIL on metal-loprotease activity, levels of interleukin-1P (IL-lp), prostaglandin E, (PGE,), and nitritehitrate in synovial fluid was determined. Methods. The OA model was created by sectioning the anterior cruciate ligament of the right stifle joint of mongrel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
178
0
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 311 publications
(195 citation statements)
references
References 35 publications
11
178
0
6
Order By: Relevance
“…Lesional joint cartilage in the placebo-treated group exhibited morphologic changes, including cartilage fibrillation and fissures, changes in cellularity, such as cloning and hypocellularity, and loss of Safranin O staining, as previously described (11,20,21) (Figure 2). A decrease in the histologic score of the medial femoral condyles, indicative of a reduced severity of the lesions, was observed in dogs with OA treated with pioglitazone (median histologic score 6.25 [range [3][4][5][6][7][8][9][10][11][12] in the placebo group versus 4.25 [range [3][4][5][6][7] in the 15 mg/day pioglitazone group and 5.5 [range [5][6] in the 30 mg/day pioglitazone group); this difference was sig- nificant following a dosage of 15 mg/day pioglitazone as compared with the placebo group (P Ͻ 0.05). This reduction in histologic scores was mainly related to a protective effect of pioglitazone treatment on the severity of structural changes and the loss of Safranin O staining.…”
Section: Characteristics Of the Experimental Animalssupporting
confidence: 76%
See 2 more Smart Citations
“…Lesional joint cartilage in the placebo-treated group exhibited morphologic changes, including cartilage fibrillation and fissures, changes in cellularity, such as cloning and hypocellularity, and loss of Safranin O staining, as previously described (11,20,21) (Figure 2). A decrease in the histologic score of the medial femoral condyles, indicative of a reduced severity of the lesions, was observed in dogs with OA treated with pioglitazone (median histologic score 6.25 [range [3][4][5][6][7][8][9][10][11][12] in the placebo group versus 4.25 [range [3][4][5][6][7] in the 15 mg/day pioglitazone group and 5.5 [range [5][6] in the 30 mg/day pioglitazone group); this difference was sig- nificant following a dosage of 15 mg/day pioglitazone as compared with the placebo group (P Ͻ 0.05). This reduction in histologic scores was mainly related to a protective effect of pioglitazone treatment on the severity of structural changes and the loss of Safranin O staining.…”
Section: Characteristics Of the Experimental Animalssupporting
confidence: 76%
“…Moreover, the increased level of NO has been linked to chondrocyte apoptosis (38,39). The role of NO in the pathophysiologic mechanisms of OA is also supported by a recent study showing that selective inhibition of iNOS could reduce the progression of experimental OA in dogs (11). This reduction of iNOS levels in OA chondrocytes by pioglitazone should also lead to reduced production of NO, and therefore this could be another factor that contributes to the positive effect of pioglitazone on the OA process.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, this finding suggests the positive influence of NO on PGE 2 synthesis in synovial joints of OA, particularly in the early stage of the disease, because the lesions observed in the experimental model are mild to moderate in severity. Also, the systemic administration of L-NIL reduced both the level of chondrocyte apoptosis and the progression of OA (12,13). Additional studies will determine whether COX inhibitors can prevent chondrocyte apoptosis in OA cartilage in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Besides causing degradation (10) or inhibiting the synthesis of cartilage matrix (11), NO may also induce chondrocyte apoptosis. We have previously reported that the systemic administration of iNOS inhibitor, N-iminoethyl-L-lysine (L-NIL), in experimentally induced OA in dogs has resulted in a reduction of articular cartilage damage and the levels of cell apoptosis and caspase-3, as determined immunohistochemically (12,13). In addition, there is a significant correlation between the level of nitrite production and the prevalence of apoptotic cells in cartilage tissue during experimentally induced OA in rabbits (14).…”
mentioning
confidence: 99%